De concordia inter codices: A Commentary - Abbass, Jobe (Studia canonica, 2016)
In his apostolic letter, De concordia inter Codices, given motu proprio, Pope Francis recognizes that the Latin and Eastern Codes have their own unique norms and that they remain mutually independent. However, for concrete pastoral reasons today, the pope is also concerned that an appropriate degree of harmony between the two Codes is necessary. To achieve this end, the motu proprio reformulates some Latin norms or adds others along the lines of the later Eastern Code. His Holiness is solicitous to do so for two specific reasons: 1) While recognizing the disciplinary peculiarities of various Churches that occur in a regional context, especially in the West, he seeks an equilibrium between safeguarding the law proper to the Eastern minority with the canonical tradition of the Latin majority; and 2) Even though the Codes generally apply only to the Catholic faithful, he aims to better define relations with the faithful of the non-Catholic Churches especially in regards to Catholic ministers’ celebration of the sacraments of baptism and marriage for non-Catholic faithful under certain conditions. In this study, the author provides a commentary of the motu proprio from its preamble, to its eleven articles and Latin canons thereby affected, to its promulgation and entry into force.